2018
DOI: 10.1038/s41598-018-34577-3
|View full text |Cite|
|
Sign up to set email alerts
|

Usefulness of peripapillary nerve fiber layer thickness assessed by optical coherence tomography as a biomarker for Alzheimer’s disease

Abstract: The use of optical coherence tomography (OCT) has been suggested as a potential biomarker for Alzheimer’s Disease based on previously reported thinning of the retinal nerve fiber layer (RNFL) in Alzheimer’s disease’s (AD) and Mild Cognitive Impairment (MCI). However, other studies have not shown such results. 930 individuals (414 cognitively healthy individuals, 192 probable amnestic MCI and 324 probable AD) attending a memory clinic were consecutively included and underwent spectral domain OCT (Maestro, Topco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 79 publications
10
61
0
Order By: Relevance
“…Importantly, by using a thorough baseline ophthalmological screening, we were able to exclude confounding from DM, glaucoma, and AMD and measure direct downstream effects of pure AD pathology on retinal structure in AD cases. These results confirm earlier analyses in our pilot cohort [7] and a recent report in a large cohort of AD and mild cognitive impairment participants [14] , while contradicting others [9] , [11] . Taken together, our results do not support the notion that retinal thickness measurements with OCT can currently serve as a diagnostic biomarker for AD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, by using a thorough baseline ophthalmological screening, we were able to exclude confounding from DM, glaucoma, and AMD and measure direct downstream effects of pure AD pathology on retinal structure in AD cases. These results confirm earlier analyses in our pilot cohort [7] and a recent report in a large cohort of AD and mild cognitive impairment participants [14] , while contradicting others [9] , [11] . Taken together, our results do not support the notion that retinal thickness measurements with OCT can currently serve as a diagnostic biomarker for AD.…”
Section: Discussionsupporting
confidence: 88%
“…OCT studies in patients with AD performed to date have presented conflicting findings [9] , [10] , [11] . Although several studies showed mean peripapillary retinal nerve fiber layer (pRNFL) thinning in AD [9] , [10] , [11] , others showed changes in single pRNFL sectors and others found no changes [12] , [13] , [14] . In addition, some studies reported absence of RNFL thinning, while thinning of total macular thickness was present [9] .…”
Section: Introductionmentioning
confidence: 99%
“…The loss of RGCs is matched with the pathologic cascade hypothesis in AD, which affects both the cerebral neuron and the RGCs in the retina (36). This whole peripapillary RNFL controversy is the result of studies based on small size samples and important methodological heterogeneity (37,(128)(129)(130). In line with this hypothesis, pattern electroretinography showed a decrease in their wave response, suggesting that RGCs are directly involved in AD (38,92,(131)(132)(133).…”
Section: Structural Changes In Admentioning
confidence: 60%
“…It is possible that retinal AD biomarkers can only be obtained after having integrated various of the already cited biomarkers, which include both neuroretinal (such as RFNL, GCL, macular thickness) and retinovascular parameters (vessel morphology among others), in a composite biomarker (128).…”
Section: Changes In the Early Ad And Their Prognostic Value In The Dementioning
confidence: 99%
“…In order to correctly interpret OCT of the retina literature results in the dementia field, it is important to have in mind that retinal thickness data obtained from different OCT devices are not readily interchangeable and it is relevant to know the average thickness and volumes obtained from the particular OCT device used in each study, which are known to be influenced by age, gender and ocular pathologies [41]. Additionally, two previous studies from our own group highlighted that OCT retinal image quality significantly differs among SCD, MCI and dementia groups and is an important predictor of OCT retinal image variability within these populations [42,43]. Still, most studies in the dementia field do not include OCT retinal image quality as a covariate in the analysis, while our data show that it would be advisable to do so.…”
Section: Discussionmentioning
confidence: 99%